Rare case of bilateral anterolateral and symmetrical bowing of tibia successfully treated with a distal tibial opening wedge osteotomy - Miranda, Margarida (J Surg Case Rep, 2019)
The anterolateral bowing of the tibia is closely associated with the development of its pseudarthrosis. Roughly, all deformities are unilateral so the shortening and angulation are easy to identify. We present a 6-year-old boy with an exuberant bilateral anterolateral bowing of tíbia. He has short stature, disturbed gait and callosity at the lateral border of the foot. Deformity was successfully treated by opening wedge tibia osteotomy and filled the remaining gap with structural fibular graft. It was fixed with two crossed K-wires and cast immobilization for 6 weeks. We decided to correct it before skeletal maturity due to the significant disturbance of the gait and esthetic impairment. It was obtained a satisfactory morphological and functional result with a simple and fast technique.